Accuracy of ICD-10 Codes for Surveillance of Clostridium difficile Infections, France - Jones, Gabrielle (Centers for Disease Control and Prevention, 2012)
The sensitivity and specificity of surveillance for Clostridium difficile infections according to International Classification of Diseases, 10th revision, codes were compared with laboratory results as standard. Sensitivity was 35.6%; specificity was 99.9%. Concordance between the 2 methods was moderate. Surveillance based on ICD-10 codes underestimated the rate based on laboratory results.